Pelatihan Tahsin Tahfidz Qur’an Di Rumah Tahfidz Qur’an At-Taqwa Masjid At-Taqwa Nusa Mappala Gowa - Ruhul Kudus; Enung Mariah S; Fatkhul Ulum; Arief Fiddienika (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
The Qur'an is the last holy book for mankind and thereafter no more holy book will be revealed by Allah. Muslims should be proud of the holy book of the Qur'an because the Qur'an is the perfect guideline for life. Every Muslim family is obliged to instill the values contained in the Qur'an to be practiced in daily life, so that every Muslim family must be able to spend special time teaching the Qur'an to its family members, both teaching carried out by the family itself and learning carried out in Islamic educational institutions. Then the Qur'an has many privileges, one of which is that reading it is a form of worship. This has been confirmed in the Qur'an Surah Fathir verse 29. In addition, Allah made the Qur'an easy to memorize and understand, as in the Qur'an surah al-Qomar verse 17. The verse hints that learning the Qur'an is the primary obligation of every believer, as well as teaching it. Memorizing the Qur'an is a good effort in maintaining the purity of the great Qur'an. By rote memorization means putting on the heart of the memorizer. The reality that occurs in the Qur'anic huffazul is that errors in the recitation of the Qur'an are not only khafi errors but also jali errors. and those mistakes are due to the lack of quality recitation and understanding of tajweed and the law of recitation before starting the process of memorizing verses of the Qur'an. The solution to the above problem is the need for training and learning Qur'an reading with the tahsin tahfidz method at the Rumah Tahfidz Qur’an At-Taqwa, At-Taqwa Mosque, Nusa Mappala, Gowa